Community based retrospective study of sex in infant mortality in India. Issue 7407 (17th July 2003) - Khanna, R; Kumar, A; Vaghela, J F; Sreenivas, V; Puliyel, J M
Abstract: Objective To determine whether the imbalance in the sex ratio in India can be explained by less favourable treatment of girls in infancy. Design Analysis of results of verbal autopsy reports over a five year period. Setting Community health project in urban India. Main outcome measures Deaths from all causes in infants aged less than 1 year. Results The sex ratio at birth was 869 females per 1000 males. The mean infant mortality was 1.3 times higher in females than in males (72 v 55 per 1000). Diarrhoea was responsible for 22% of deaths overall, though twice as many girls died from diarrhoea. There were no significant differences in the numbers of deaths from causes such as birth asphyxia, septicaemia, prematurity, and congenital anomalies. In 10% of deaths there was no preceding illness and no satisfactory cause was found. Three out of every four such deaths were in girls. Conclusions The excess number of unexplained deaths and deaths due to treatable conditions such as diarrhoeal disease in girls may be because girls are regarded and treated less favourably in India.